Co-treatment of residential and oil and gas production wastewater with a hybrid sequencing batch reactor-membrane bioreactor process. (June 2017) - Frank, Victoria Bennett; Regnery, Julia; Chan, Kevin E.; Ramey, Dotti F.; Spear, John R.; Cath, Tzahi Y.
Graphical abstract: Highlights: An SBR-MBR was used to co-treat residential and O&G wastewater for beneficial reuse. Produced water can be treated without negatively affecting treatment up to 6% by volume. Nitrification was lost when 20% produced water by volume was dosed to the system. Trace organic compounds were still biologically removed in the presence of produced water. Heavy metals were removed and not accumulated in the biosolids. Abstract: Exploration and production of oil and gas (O&G) generates large volumes of wastewater. High salinity and the presence of both dissolved constituents and suspended solids require complex and expensive treatment of O&G produced waters for beneficial reuse (e.g., fracking, irrigation, surface water discharge). Nearly 90% of wastewater produced during the lifetime of O&G wells is currently disposed of due to the high cost of treatment; thus, simple and inexpensive treatment technologies and approaches must be developed to promote water reuse in the O&G industry. In this study we investigated the potential for publicly owned wastewater treatment plants to co-treat produced water and residential waste-water. The removal of organic compounds, nutrients, metals, trace organic compounds, and suspended solids from the combined stream was investigated using a pilot-scale hybrid sequencing batch reactor-membrane bioreactor system. Produced water was initially dosed at 6% by volume, and comparable removal of primary (i.e., chemical oxygen demand, ammonia) and secondary constituents (i.e., trace organic compounds, inorganic contaminants) to control conditions was achieved. When produced water was increased to 20% of the influent by volume, nitrification was lost; however, the dominant biological communities in the bioreactors remained stable, providing evidence of an adaptive system and reliance on non-dominant microorganisms to achieve optimal treatment.